A manager's guide to using the force : leadership lessons from a galaxy far far away - Urick, Michael J. (Exploring effective leadership practices through popular culture, 2021)
Part of the series Exploring Effective Leadership Practices through Popular Culture, Urick examines management theories related to mentorship and learning, transformational and transactional leadership, ethical decision making, bases of power, mindfulness, multi-tasking, and more. As you learn to apply these theories, you can become at one with the Force to find balance in your leadership style. Each theory is viewed through the lens of various aspects of the Jedi approach to exerting influence. Through these examples, readers will become familiar and comfortable with academically supported leadership concepts to adjust their own behaviors, becoming more successful in the process. By examining leadership theories through the context of popular culture, the book encourages readers to think creatively about how they might adjust their own management approach. Readers will move from Padawan to Master quickly. May the Force be with you, Jedi Manager! The series aims to bring examples, theory and methodology of leadership to life by analysing academic concepts through popular culture examples that will appeal to a broad range of readers.